BIOLOGY ESSAY QUESTIONS: COGNITIVE LEVEL AS REVEALED BY BLOOM’S TAXONOMY: Received: 22nd April 2021; Revised: 07th August, 28th September 2021, 6th January 2022; Accepted: 12th January 2022 - Azzopardi, Marthese; Azzopardi, Carmel (PUPIL: International Journal of Teaching, Education and Learning, 2022)
Examination questions indicate the cognitive level anticipated from students. Although essays have the potential to test higher cognitive skills, the extent of their effectiveness in assessing these is not clear. The objective of this study was to estimate how well Biology essay questions measure higher-order cognitive skills in a public post-secondary institution in Malta. The essay questions were classified into cognitive levels based on Bloom’s Revised Taxonomy and categorized as those demanding lower-order thinking skills (LOTS) and higher-order thinking skills (HOTS). No essays from the Applying and Creating objectives were recorded. Except for one year, questions from at least three cognitive objectives were present in each examination paper. Results showed that questions from the Remembering cognitive objective predominated. Some topics comprised 100% LOTS but others were from three objectives. These results indicate that paper setters attempt to design essay titles that belong to various cognitive objectives, but more attention should be dedicated to diversifying. The value of this study is that examiners have a database to choose a mixture of LOTS and HOTS in future examinations, rendering them more effective. The findings highlight the importance for examiners to use Bloom’s Revised Taxonomy when constructing questions.